The Impact of firm type, size and experience on professional services of architectural firms in Nigeria / Aluko Olusola Raphael, Omoniyi Sunday Samuel and Dipeolu Adedotun Ayodele. - Raphael, Aluko Olusola; Samuel, Omoniyi Sunday; Ayodele, Dipeolu Adedotun (Universiti Teknologi MARA, Shah Alam, 2019)
Clients have expressed dissatisfaction about services of professionals as a result of poor quality of service and errors in documentations resulting into overrunning project cost and delayed completion. This study investigated the influences of firms’ types, size of firms and experience of firms on provision of professional services of Architectural firms in the process of meeting the expectations of the client. Questionnaires was used to collect data for the study through random sampling. The results of ANOVA showed that firm types had no significance on services across the stages of service, firm size showed significance while the experience of the firm showed significance across the inception and the design stages. Multiple regression analysis showed that the variables cumulatively explained 3.9% (at p < 0.05) of the variance in the overall professional services of architectural firms. Among the variables, only the firm size showed a significant impact on the overall professional services with a p-value of 0.003. The firm type and experience of firm had no impact on the overall professional services. The findings serve as a guide to the clients in making choice of consultancy firms for their project, and as a guide to the consultancy firms in order to remain competitive in the globalized industry.